2018
DOI: 10.1016/j.ijmultiphaseflow.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of the spraying processes in improved design of effervescent atomizer

Abstract: This work experimentally examines the primary atomization processes in a newly developed atomizer, similar to effervescent atomizer concept, at low pressures and low gas-to-liquid ratios (GLR). Several experimental and post-processing techniques are applied to investigate the spray spatial evolution. The near-nozzle area is captured by a high-speed camera with a long-distance microscope. Further, characteristics of the developed spray are investigated by a phase-Doppler analyser (PDA). The high-speed recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…As our previous work Mlkvik et al [21] revealed, the investigated OIL configuration proved that the injection port configuration has a significant influence on the performance of the atomizer. This was later confirmed by Zaremba et al [22]. The CFT ( Figure 1c) nozzle has a design inspired by several previous works Chin [31], Ferreira M. Teixeira [32], Tamaki N.and Shimizu [33].…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…As our previous work Mlkvik et al [21] revealed, the investigated OIL configuration proved that the injection port configuration has a significant influence on the performance of the atomizer. This was later confirmed by Zaremba et al [22]. The CFT ( Figure 1c) nozzle has a design inspired by several previous works Chin [31], Ferreira M. Teixeira [32], Tamaki N.and Shimizu [33].…”
Section: Introductionmentioning
confidence: 52%
“…With regard to the values of We mix , Bo mix and the Fr mix (Table 2), the OIL device was characterized by the dominant influence of fluid inertia and gravity on the internal flow. The internal flow pattern was identified as the wall-attached [16,21,22], Figure 7a). The internal two-phase flow pattern led to the continuous passage of the liquid film through the discharge orifice without significant GLR fluctuations [15].…”
Section: Spraying At Low Glrmentioning
confidence: 99%
See 2 more Smart Citations
“…In IMP atomizers, atomization gas and liquid stream are brought into contact in a mixing zone inside the atomizer and leave the atomizer through the exit orifice in a two-phase flow pattern. For this purpose, several gas injection geometries have been proposed (e.g., [15,17,[20][21][22][23]). Although no targeted mixing of gas and liquid is performed in most cases [24], it is well known for IMP atomizers that internal flow conditions determine the means of liquid disintegration and the spray development in time and space [22].…”
Section: Introductionmentioning
confidence: 99%